Rynek kredytowy w Polsce w warunkach integracji europejskich rynków - Sidor, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of elaboration is a presentation of credit market in Poland in an aspect of its activity on European financial market. Brokerage and counseling credit trade in Poland, in terms of European integration of financial markets, is situated in a phase determined by quick development of its performance. Mortgages credits are one of the fastest developing segments in polish credit market. The competition in this area is still tightening, what leads to decreasing prices of a credit and liberalization of the procedure of applying for a credit.